Design and fabrication of mechanical floor cleaner / Muhamad Arif Jailan - Jailan, Muhamad Arif (2023)
Some cleaning contractors in small groups, such as school cleaning companies, suffer back pain from using only conventional mops for too long. The school also has a large area, such as a hall and a sports court, such as a badminton court and a futsal court, and they had to clean that area by only using a conventional mop. If a school cleaning company wants to make it easier, they need to buy a floor scrubber; it's too expensive and not worth it. The main purpose of our project is to create an inexpensive floor cleaner that works the same as other floor scrubbers on the market and can also replace existing conventional mops. This project uses the concept of a machine floor scrubber and realizes it in a trolley concept. This project also can be marketed at a lower price than existing floor scrubbers. This will reduce the burden of small cleaning contractors, such as in schools and, at the same time, can overcome the pain and difficulty they experience when using a conventional mop.